Permainan edukasi : Tarian Barong Ket Bali - Andika Mahendra Tanggulouw; Sumenge Tangkawarouw Godion Kaunang; Virginia Tulenan (Universitas Sam Ratulangi, 2021)
Abstract — Indonesia has a diversity of tourism, culture and beautiful arts in every region, one of which is Bali. Bali has very beautiful tourist attractions, as well as Balinese art and culture, one of which is the barong ket dance. In every dance, it is not only the beauty of the dance movements but also the meaning contained therein. Local culture and arts are things that must be preserved by the younger generation. In preserving culture by taking advantage of technological developments, one of the games is very fast in this era, such as game based education with the aim of helping the learning process in a fun way. This study aims to design an interesting and fun game based education that explains the barong ket dance using the Multimedia Development Life Cycle (MDLC) method. Based on the results of the evaluation of this game research, it can be an interesting learning medium and can add new knowledge about the meaning and meaning of the Barong Ket dance. Keyword — Game Based Education; 3D Game; Multimedia Development Life Cycle; Barong Ket Dance. Abstrak — Indonesia memiliki keanekaragaman wisata, kebudayaan dan kesenian yang indah disetiap daerah salah satunya di Bali. Bali memiliki tempat wisata yang sangat indah, begitu juga dengan seni dan kebudayaan Bali salah satunya tarian barong ket. Dalam setiap tarian tidak hanya sekedar keindahan gerakan tarinya namun juga makna yang terkandung didalamnya. Kebudayaan dan kesenian daerah adalah hal yang harus dilestarikan oleh generasi muda. Dalam melestarikan kebudayaan dengan memanfaatkan perkembangan teknologi yaitu salah satunya game yang sangat pesat pada zaman ini seperti game based education dengan tujuan untuk membantu proses pembelajaran secara menyenangkan. Penelitian ini bertujuan untuk merancang sebuah pendidikan berbasis aplikasi permainan yang menarik dan menyenangkan yang menjelaskan tentang tarian barong ket dengan menggunakan metode Multimedia Development Life Cycle (MDLC). Berdasarkan hasil evaluasi penelitian game ini dapat menjadi media belajar yang menarik dan dapat menambah pengetahuan baru tentang arti dan makna Tarian Barong Ket. Kata kunci — Pendidikan berbasis aplikasi permainan; Game 3D; Multimedia Development Life Cycle; Tarian Barong Ket